Investigating routine care non-pharmacological treatment for adolescents with ADHD - Sibley, Margaret H.; Reyes Francisco, Juan Carlos; Rios-Davis, Alexandria; Graziano, Paulo A. (Frontiers in Health Services, 2022)
Objective: To characterize routine non-pharmacological care for youth with ADHD. Methods: 76 audio-recorded work-samples were collected from community mental health therapists in a large metropolitan area in the United States and were analyzed for operationally defined practice elements commonly included in evidence-based non-pharmacological treatment for ADHD. Analyses characterized community provider practices and examined predictors of using evidence-based (vs. low-value) practices. Results: Individually delivered social skills training was the most commonly detected practice element (31.6% of practice samples). Parent involvement in routine care was uncommon (53.9% of sessions had no parental presence). Core elements of evidence-based practices were rarely delivered (e.g., organization skills training: 18.4% of tapes; operant reinforcement: 13.2%); when evidence-based content was introduced, it was typically implemented at a very low intensity. Patient and provider characteristics did not predict use of evidence-based practices. Conclusions: Routine non-pharmacological care for adolescent ADHD primarily consisted of low value practices such as youth-directed treatment and social skills training with low parent involvement and only occasional therapy homework. To improve quality of care, efforts to de-implement low value practices should be coupled with efforts to implement evidence-based practices (i.e., parent involvement, measurement-based care, organization skills training, use of operant reinforcement).